Eletromemória: um aplicativo de jogo de memória como proposta de ferramenta didática para o ensino de tópicos em eletrodinâmica - LIMA, Layane Do Nascimento (2022)
This study deals with the use of a didactic game application called “ELECTROMEMORY” for teaching physics, covering a good part of the contents of electrodynamics as a tool that will help to assess student learning in physics classes. The project developed aims to investigate how the integration of technologies in Physics education can be provided through the use of an installed application to run on mobile devices such as smartphones and tablets. The justification for the proposal of this product arose from the doubt whether it would be possible to observe the learning of the student in the 3rd year of high school through the application of Educational Game (application) in the teaching of physics in relation to the content of electrodynamics? Therefore, a didactic game was applied in an application version of a game software using the Java programming language being developed on Android, proposing that it could be played offline. The game was evaluated through a questionnaire by Professors who teach high school in public and private schools in the state of Piaui and Maranhão, with the aim of evaluating it before being applied to third grade high school students. Soon after, it was applied to third grade high school classes at the Santo Dumont Teaching Center in Caxias – MA. Before and after using the game in the classroom, a questionnaire was applied in order to assess its efficiency as a potentially significant material. To complete this investigation, a statistical treatment was carried out with the data collected and from these data, it was noted that most teachers considered the game a great contribution in a significant way for effective student learning. The results show that the game presents the main characteristics of a recreational activity and the necessary aspects for its characterization as an educational game. It is still possible to conclude that the game aroused the student's interest in Electrodynamics, they considered the game fun and easy to install.